PENGINGAT LAYANAN PESAN SINGKAT SEBAGAI EDUKASI BAGI PELAJAR SMP YANG MEROKOK DI KOTA PEMATANGSIANTAR - Julia Alistawaty Purba; Kintoko Rochadi; Juanita Juanita (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: this study aims to analyze the influence of short message service reminder on knowledge of junior high school students who smoked in Pematangsiantar City. Method: the type of study is quasi experiment with a pretest-posttest design. The population was all junior high school students who smoked, and 85 of them were used as the samples. The data were analyzed by using Wilcoxon statistic test. Result: The result of this study showed that the mean value of knowledge from 1.48 to 2.36 at p-value=0.0001 which indicated that there was the influence of short message service reminder on knowledge of the junior high school students who smoked in Pematangsiantar City. Conclution: it is necessary to educated for health information exposure with continuously and sustainably as the promotive and preventive effort such as short message service reminder.